2017
DOI: 10.1038/s41598-017-15040-1
|View full text |Cite
|
Sign up to set email alerts
|

ACVR2B/Fc counteracts chemotherapy-induced loss of muscle and bone mass

Abstract: Chemotherapy promotes the development of cachexia, a debilitating condition characterized by muscle and fat loss. ACVR2B/Fc, an inhibitor of the Activin Receptor 2B signaling, has been shown to preserve muscle mass and prolong survival in tumor hosts, and to increase bone mass in models of osteogenesis imperfecta and muscular dystrophy. We compared the effects of ACVR2B/Fc on muscle and bone mass in mice exposed to Folfiri. In addition to impairing muscle mass and function, Folfiri had severe negative effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
71
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 123 publications
13
71
0
1
Order By: Relevance
“…Advanced OC patients often experience the symptoms of cachexia, an extremely debilitating condition mainly responsible for body weight loss, severe muscle and fat wasting, fatigue, decreased response to antineoplastic therapies, and overall reduced survival . We and others showed that counteraction of cachexia by means of pro‐anabolic agents prevents chemotherapy side toxicities in skeletal muscle and promotes better survival in cancer hosts, despite limited or no effects on tumour size . This also suggests that preservation of skeletal muscle mass per se may benefit quality of life and survival in patients with cancer.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Advanced OC patients often experience the symptoms of cachexia, an extremely debilitating condition mainly responsible for body weight loss, severe muscle and fat wasting, fatigue, decreased response to antineoplastic therapies, and overall reduced survival . We and others showed that counteraction of cachexia by means of pro‐anabolic agents prevents chemotherapy side toxicities in skeletal muscle and promotes better survival in cancer hosts, despite limited or no effects on tumour size . This also suggests that preservation of skeletal muscle mass per se may benefit quality of life and survival in patients with cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Administration of ACVR2B/Fc was shown to completely restore muscle wasting in this model . ACVR2B/Fc is an inhibitor of the Activin Receptor 2B signalling known to preserve muscle mass and prolong survival in tumour hosts and to increase muscle and bone mass following chemotherapy treatment . However, based on the results of a recent genomic profiling, the TOV‐21G tumours were found to possess few copy number alterations and a ‘hyper‐mutated’ genome, thus setting this cell type apart from the rest of the OC cell lines and from the HGS‐OC tissue samples …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Doxorubicin and carboplatin chemotherapies have been used to study musculoskeletal changes and have revealed that these agents alone cause significant reduction in bone volume . The combination therapy Folfiri (5‐fluorouracil, leucovorin, and irinotecan) also causes reduced bone volume …”
Section: Bone Loss In Cancer Patientsmentioning
confidence: 99%